Relevansi Surat Edaran Menteri Agama Tentang Pedoman Pengeras Suara Di Masjid/Mushollah Dalam Mengimplementasikan Toleransi Umat Beragama Kota Lubuklinggau - Sapardi Sauti; Rama Wijaya Kesuma Wardani; Umar Maliki; Della Pudralisa (STAI Bumi Silampari, 2022)
The issuance of a circular letter from the minister of religion regarding the rules for loudspeakers in mosques/mushollah indeed brings many positive and negative sides. Each resident has the choice to decide to admit or dismiss. This small-scale research is planned to find out and understand the fairness of issuing circulars from scholars regarding the rules for loudspeakers in mosques or rooms asking for God with the peculiarities experienced by non-Muslim community groups in the city of Lubuklinggau. Therefore, leading research is very important. The right exploration strategy for us to use in overcoming these problems is a subjective examination technique that puts forward interviews (interviews). From the consequences of our exploration, it is possible to reason that the circular letter of the religious pastor regarding the rules for amplifiers in the mosque/mushollah in the view of non-Muslim groups in Lubuklinggau is very relevant. less applicable. This is because there is only one respondent who feels helped by the circular letter. Meanwhile, 1 other respondent felt that the round had no impact, and surprisingly, 1 other reaction emphatically rejected it.